ANALISIS KEDUDUKAN PERATURAN DESA DAN PEMBENTUKAN PERATURAN DESA YANG DEMOKRATIS PARTIPATORIS - BAHARUDIN BAHARUDIN (KEADILAN PROGRESIF, 2019)
The position of village regulations after ratification of Law Number 6 of 2014concerning Village Regulations is as Legislation Regulations other than legislation listed inthe hierarchy in accordance with Article 7 paragraph (1) of Law Number 12 of 2011. VillagePostal Regulations ratified by Law Number 6 of 2014 no longer domiciled only as a furtherelaboration of the higher Regulations, but has been placed as recognized legislation. Theformation of a democratic perdes must reflect community participation. will avoid adverseeffects on the village community. Issues regarding How the Position of Village Regulations,How the Democratic Formation of Village Regulations The results of the discussion can beelaborated, The Position of Village Regulations The Hierarchical Legislation System TheVillage Regulatory System is no longer explicitly referred to as a type of regulation. Thismeans that the position of village regulations is considered only as a further elaboration ofhigher laws and regulations, but there is no local government to provide villageempowerment. The process of establishing democratic Village Regulations, Village Headsand BPD, must involve village structures (village officials), RW, RW and communitymembers. Formation of good village regulations, based on the substance of villageregulations, namely: principles of good village governance, namely, legal certainty, orderlyimplementation of village governance, public interests, openness, proportionality,professionalism, accountability, local livelihoods, diversity , and Participation. Suggestionsthat the Village Head and BPD in making village regulations, must be democratic, bypresenting community participation, community leaders, traditional leaders, religiousleaders and women in the village.